IDENTIFICATION OF SCHOOL BULLYING BEHAVIOR IN HIGH GRADE STUDENTS OF STATE ELEMENTARY SCHOOL 001 BALAM JAYA KAMPAR - Rezinanda Saprila (Yayasan Thaifah Manshurah Pekanbaru, 2022)
This study aims to further identify bullying behavior in schools in the 001 Elementary High School Balam Jaya Kampar. This study uses a quantitative descriptive method. For the aspect of direct physical contact has the highest percentage of 90.26% with the